SURVEI TINGKAT PENGETAHUAN PASAR MODAL PADA MASYARAKAT PERGURUAN TINGGI DI KOTA BANJARMASIN - Rofinus Leki; Firda Rosita (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2020)
The Survey Financial Services Authority2016 that capital market literacy in Indonesia is still low when compared to banking and other financial institutions. The purpose of this research is to examine the level of knowledge of the community of Higher Education in the Banjarmasin city about capital market literacy. This research was conducted by survey method by distributing questionnaires to 210 people of the Higher Education community consisting of lecturers, administrative staff, and students. The results of the study revealed that the community of Higher Education in the Banjarmasin city had a level of knowledge in the category of literate sufficent towards the Capital Market and Financial Institutions related to the Capital Market. Therefore, the Indonesia Stock Exchange together with securities companies should increase the intensity of technical and fundamental analysis training programs in order to improve the skills of tertiary institutions in utilizing the capital market.